Peripartum Cardiomyopathy (PPCM): How to Diagnose and Deal with? - Monika Sitio; Cholid Tri Tjahjono; Heny Martini; Novi Kurnianingsih (Heart Science Journal, 2021)
Peripartum cardiomyopathy (PPCM) is a diagnosis of exclusion, where patients present with heart failure (HF) secondary to left ventricular (LV) systolic dysfunction without any other cause of HF identified in the last month of pregnancy or within first five months after delivery, abortion, or miscarriage. PPCM is a life-threatening condition which frequently under diagnosed and inadequately treated, whereas the morbidity and mortality rate ranges between 7% and 50%. Early diagnosis is important to decrease morbidity and mortality. Therefore, it is necessary to report the case related to this condition.A 34-year-old woman was referred to RSSA with worsening shortness of breath (SOB). She has given birth about 2.5 months prior to admission. History taking and supporting findings form this case were supported to diagnosis of PPCM. She was treated with diuretic, aldosterone antagonist, ACE-I, beta blocker, anticoagulant, and bromocriptine. The symptoms were improved in the following days. She was discharged with better condition and educated to comply with medication.